2008
DOI: 10.1111/j.1551-2916.2008.02753.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Optimization of Lithia–Alumina

Abstract: The optimization of thermodynamic parameters in the Li 2 O-Al 2 O 3 system using available thermodynamic and assessed phase diagram data is discussed. A procedure for obtaining a suitable associate species solution model for the liquid in this system is presented. It is shown that if the eutectic near the pure alumina composition is ignored during the optimization, the optimized thermodynamic parameters in this system result in a phase diagram that is in reasonable agreement with the experimental one. Optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…According to our study, these areas were also oxygen-rich regions. As seen in Figure 4a and b, EDS maps at a higher resolution showed that the compounds at the grain boundary and in the smaller particles mainly contained [46], a eutectic composition with 23 mol% Al 2 O 3 is formed that has a melting temperature of 1055°C, which is lower than the sintering temperature (i.e., 1100°C) in our study.…”
Section: Morphology and Elemental Analysismentioning
confidence: 42%
“…According to our study, these areas were also oxygen-rich regions. As seen in Figure 4a and b, EDS maps at a higher resolution showed that the compounds at the grain boundary and in the smaller particles mainly contained [46], a eutectic composition with 23 mol% Al 2 O 3 is formed that has a melting temperature of 1055°C, which is lower than the sintering temperature (i.e., 1100°C) in our study.…”
Section: Morphology and Elemental Analysismentioning
confidence: 42%
“…Upon heating to 900 °C, the thermodiffraction pattern exhibited the formation of γ-LiAlO 2 (JCPDS 38-1464). The Li 5 AlO 4 decomposed to form γ-LiAlO 2 , which may have occurred via the sublimation of lithium, according to the following reaction : Li 5 AlO 4 ( s ) 4 Li false( normalg false) + normalO 2 ( g ) + LiAlO 2 ( s ) …”
Section: Resultsmentioning
confidence: 99%
“…Figure S1 in Supplementary Information (SI) shows the phase diagram of Al2O3-Li2O optimized by Kulkarni and Besmann. 33 As one can see that these lithium aluminates are stable at wide range of temperatures although with increasing the ratio of Li2O:Al2O3 the melting temperature is decreased. In addition, the Al2O3-Na2O and Al2O3-K2O have similar phase diagrams.…”
Section: Introductionmentioning
confidence: 93%